Does accounting education affect professional skepticism and audit judgment? - Dewi Fatmawati,; Arizona Mustikarini,; Fransiska, Inneke Puspita (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study examines the extent to which enrollment in accounting programs influences students’ skepticism levels. We compare the skepticism scores between final-year accounting students in undergraduate and professional programs. This study also investigates the impacts of trait skepticism and situational skepticism on the participants’ initial judgment of fraud or errors. Situational skepticism in this study is represented by audit experience from previous years. This study employs an experimental design of 2x3 between-subjects, where trait skepticism is divided into higher and lower levels, and the audit experience from previous years is manipulated into positive, negative and neutral. The participants in this study are 227 accounting students from both undergraduate and professional programs. The results of this study show that accounting students in the professional program are likely to exhibit higher levels of trait skepticism compared to their counterparts in the undergraduate program. The results also indicate that participants make an audit judgment based mainly on their prior experience with the client, not on their trait skepticism. This propensity is more salient particularly in the case of the less-skeptical participants. In sum, the higher that the formal education of a participant is, then the higher is his/her trait skepticism, and thus he/she is able to retain his/her skeptical judgments regardless of his/her prior experience with the client.